An exploratory study on the possibility of misappropriation of assets occurring in a local authority. A preliminary study on the misappropriation of assets in local authority in Malaysia / Rozaiha Ab Majid … [et al.] - Ab Majid, Rozaiha; Mohamed, Nafsiah; Abdullah, Azizah; Mahmud, Zanariah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Over the years, local authorities in Malaysia have been saddled with more responsibilities especially with the increasing number of fraud cases reported. While the discussion of fraud in local authorities usually focuses on corruption, this paper takes light on misappropriation of assets. The findings from a survey and an interview revealed that misappropriation of assets was a problem to the selected local authority and the likelihood of misappropriation of assets to occur in the future was high.